Impact of comorbidities on survival following major injury across different types of road users. Issue 10 (October 2022) - Shu, C.C.; Dinh, M.; Mitchell, R.; Balogh, Z.J.; Curtis, K.; Sarrami, P.; Singh, H.; Levesque, J.-F.; Brown, J.
Highlights: Among road users with major trauma, those with higher Charlson Comorbidity Index score, cardiovascular diseases and diabetes were more likely to die, regardless of age and road user type. The association between death and cardiovascular diseases was stronger in males than females. Pedestrians with severe injury (ISS ≥25) and severe impaired consciousness (GCS total score 3-8) were more likely to die, regardless of pre-existing comorbidities or age, compared to car occupants. Our findings highlight the need to identify ways to enhance the management of road trauma patients with pre-existing cardiovascular diseases, diabetes, or multiple comorbidities, as well as the need to prioritize actions to prevent pedestrian crashes in strategies to reach Vision Zero. Abstract: Background: While comorbidities and types of road users are known to influence survival in people hospitalised with injury, few studies have examined the association between comorbidities and survival in people injured in road traffic crashes. Further, few studies have examined outcomes across different types of road users with different types of pre-existing comorbidities. This study aims to examine differences in survival within 30 days of admission among different road user types with and without different pre-existing comorbidities. Method: Retrospective cohort study using data for all major road trauma cases were extracted from the NSW Trauma Registry Minimum Dataset (1 January 2013 – 31 July 2019) and linked to the NSW Admitted Patient Data Collection, and the NSW Registry of Births, Deaths and Marriages - death dataset. Pre-existing comorbidities and road user types were identified by the International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, Australian Modification (ICD-10-AM) codes and Charlson Comorbidity Index in the Trauma Registry, hospital admission, and death datasets. Logistic regression was used to assess the associations between six types of road users (pedestrian, pedal cycle, two- and three-wheel motorcycle, car and pick-up truck, heavy vehicle and bus, and other types of vehicle) and death within 30 days of hospital admission while controlling for comorbidities. All models used 'car and pick-up truck driver/passenger' as the road user reference group and adjusted for demographic variables, injury severity, and level of impaired consciousness. Results: Within 6253 traffic injury person-records (all aged ≥15 years old, ISS>12), and in final models, injured road users with major trauma who had a history of cardiovascular diseases (including stroke), diabetes mellitus, and higher Charlson Comorbidity Index score, were more likely to die, than those without pre-existing comorbidities. Furthermore, in final models, pedestrians were more likely to die than car occupants (OR: 1.68 – 1.77, 95CI%: 1.26 – 2.29 depending on comorbidity type). Conclusions: This study highlights the need to prioritize enhanced management of trauma patients with comorbidities, given the increasing prevalence of chronic medical conditions globally, together with actions to prevent pedestrian crashes in strategies to reach Vision Zero.